2019
DOI: 10.3390/diagnostics9020048
|View full text |Cite
|
Sign up to set email alerts
|

HAMP Downregulation Contributes to Aggressive Hepatocellular Carcinoma via Mechanism Mediated by Cyclin4-Dependent Kinase-1/STAT3 Pathway

Abstract: Background: Hepcidin encoded by HAMP is vital to regulating proliferation, metastasis, and migration. Hepcidin is secreted specifically by the liver. This study sought to examine the functional role of hepcidin in hepatocellular carcinoma (HCC). Methods: Data in the Cancer Genome Atlas database was used to analyze HAMP expression as it relates to HCC prognosis. We then used the 5-ethynyl-20-deoxyuridine (EdU) incorporation assay, transwell assay, and flow cytometric analysis, respectively, to assess proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Their results suggested that by lowering liver HAMP levels, HCC cells could secure abundant iron from sources such as enterocytes and macrophages. Shen et al [ 12 ] reported that low HAMP expression is linked with higher rates of metastasis and poor disease-free status in HCC, and that the role of HAMP in cellular proliferation and metastasis is related to cell cycle checkpoints. The group proposed that HAMP serves as a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…Their results suggested that by lowering liver HAMP levels, HCC cells could secure abundant iron from sources such as enterocytes and macrophages. Shen et al [ 12 ] reported that low HAMP expression is linked with higher rates of metastasis and poor disease-free status in HCC, and that the role of HAMP in cellular proliferation and metastasis is related to cell cycle checkpoints. The group proposed that HAMP serves as a tumor suppressor gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not measure it on this occasion because hepcidin expression as a standalone or the effect of iron on hepcidin in HepG2 cells has been previously examined by various groups 20 , 21 , 43 51 . In addition, we already know that hepcidin expression is diminished in hepatocellular carcinoma, unlike other cancers, and its reduction contributes to the aggressiveness of the disease 52 , 53 . We also know the significance of hepcidin-ferroportin axis in metastasis where hepcidin is thought to play a contributory role in promoting cancer cell homing and fostering metastasis 54 .…”
Section: Discussionmentioning
confidence: 99%
“…In human HCC cell lines, iron enhances proliferation and iron deprivation leads to cell cycle arrest and increased apoptosis [110] . It has been reported that increased iron concentration in HCC cells was associated with enhanced migration, invasion, high metastasis rate and recurrence [111] .…”
Section: Mechanisms Of Iron Toxicity In Hh Leading To Hccmentioning
confidence: 99%